KONDISI SOSIAL EKONOMI KELUARGA PETANI CACAO DI KENAGARIAN SIKUCUR KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Yulmaita, Yulmaita; Juita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This  study  aimed  to  obtain  information  on  data  on  Socio-Economic  Condition  Family Farmers Cacao In Kenagarian Sikucur District V Koto Kampung Dalam. Discuss about 1) the state of education in the whole family Kenagarian Sikucur cacao farmers, 2) the condition of cacao  farm  family  income,  3)  cacao  farmers  work  conditions,  and  4)  the  condition  of ownership of family assets cacao farmers in Kenagarian Sikucur In District V Koto Kampung Padang Pariaman district .Classified research on descriptive research, family research subject is  that  cacao  farmers  in  Kenagarian  Sikucur.  Kenagarian  Sikucur  consisting  of  fourteen surroundings.  The  sampling  technique  used  is  the  sample  of  respondents.  the  number  of respondents  in  this  study  was  104  households.  Data  collection  techniques  used  were interviews and observation,   data collection tools  by using a questionnaire study. Techniques of  data  analysis  is  descriptive  in  the  form  of  a  percentage  formula.   Results  of  this  study include : 1) the state of education cacao farmers in general not just at the level of  junior high school  -  graduate  (74  %)  and  upper  middle  as  many  (72.9  %),  2)  The  condition  of  high category cacao farmers income is  Rp. > 1,000 .000-1.250.000 (65.3 %) and Rp. > 1,250,000 (30.7 %) , 3) Conditions before farming cacao farmers work in general farming and coconut rice (75.8 %), with a side jo b trade and the self-employed (82.6 %), 4 ) the condition of assets cacao farmers in general have two vehicles per household (58.6 %), type of house most of the permanent  farmers  (84.6 %)  homes  (53.8  %)  and  the status of  the  land  or  land  planted  in cacao are generally owned their own (73.0 %) .